Belief, delusion, hypnosis, and the right dorsolateral prefrontal cortex: A transcranial magnetic stimulation study. (April 2018) - Coltheart, Max; Cox, Rochelle; Sowman, Paul; Morgan, Hannah; Barnier, Amanda; Langdon, Robyn; Connaughton, Emily; Teichmann, Lina; Williams, Nikolas; Polito, Vince
Abstract: According to the Two-Factor theory of delusional belief (see e.g. Coltheart at al., 2011), there exists a cognitive system dedicated to the generation, evaluation, and acceptance or rejection of beliefs. Studies of the neuropsychology of delusion provide evidence that this system is neurally realized in right dorsolateral prefrontal cortex (rDLPFC). Furthermore, we have shown that convincing analogues of many specific delusional beliefs can be created in nonclinical subjects by hypnotic suggestion and we think of hypnosis as having the effect of temporarily interfering with the operation of the belief system, which allows acceptance of the delusional suggestions. If the belief system does depend on rDLPFC, then disrupting the activity of that region of the brain by the application of repetitive transcranial magnetic stimulation (rTMS) will increase hypnotizability.Dienes and Hutton (2013) have reported such an experiment except that it was left DLPFC to which rTMS was applied. An effect on a subjective measure of hypnotizability was observed, but whether there was an effect on an objective measure could not be determined. We report two experiments. The first was an exact replication of the Dienes and Hutton experiment; here we found no effect of rTMS to lDLPFC on any hypnotic measure. Our second experiment used rTMS applied to right rather then left DLPFC. This right-sided stimulation enhanced hypnotizability (when hypnotic response was measured objectively), as predicted by our hypothesis. These results imply a role for rDLPFC in the cognitive process of belief evaluation, as is proposed in our two-factor theory of delusion. They are also consistent with a conception of the acceptance of a hypnotic suggestion as involving suspension of disbelief.